Product standardization of tuna (Thunnus albacarres) burger - Pangilinan Josefina Dominguez
ABSTRACT This study was designed to standardize a burger made from tuna meat. Phase I involved laboratory scale production of the Bureau of Fisheries and Aquatic Resources (BFAR) formulation and its subsequent evaluation by laboratory panelists. This was done to assess the product, that is to get a description of its attributes, and consequently to find out if improvements were necessary. The end product of this phase had light brown color, ideal texture, aroma, flavor strength, and were moderately liked by the panelists. There was no improvement necessary. Phase II involved the translation of the production from a laboratory scale of one kilo to a pilot scale of five kilos per production batch to test the adaptability of the formulation and process to an increased volume of production. This phase also included objective and microbial test on the finished product, as well as product costing.